1999
DOI: 10.1002/(sici)1097-461x(1999)74:3<343::aid-qua7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active fullerene derivatives: Computations of structures, energetics, and vibrations of C60(OH)x and C60(NO2)y

Abstract: ABSTRACT:This article reports quantum-chemical semiempirical computations of selected multihydroxy and multinitro derivatives of C . Polyhydroxylated fullerenes 60 have been known for their efficient free-radical scavenging activity and promising results in reducing the concentration of free radicals in pathological blood and in inhibiting the growth of abnormal cells. Nitro-fullerenes are directly linked to hydroxy-fullerenes as polyhydroxylated fullerenes can be produced through hydrolysis of polynitro-fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
(1 reference statement)
2
11
0
Order By: Relevance
“…Finally, although an overwhelming majority of computational evaluations for fullerenes and metallofullerenes has been based on potential energy only, this study presents a topical example of the deeper insight offered by the Gibbs-energy based evaluation. The temperature evolution of the Ca@C 82 system exhibits two features already known 54 for the isomeric hollow fullerenes. Relative stability interchanges can occur with increasing temperature.…”
Section: Resultsmentioning
confidence: 71%
“…Finally, although an overwhelming majority of computational evaluations for fullerenes and metallofullerenes has been based on potential energy only, this study presents a topical example of the deeper insight offered by the Gibbs-energy based evaluation. The temperature evolution of the Ca@C 82 system exhibits two features already known 54 for the isomeric hollow fullerenes. Relative stability interchanges can occur with increasing temperature.…”
Section: Resultsmentioning
confidence: 71%
“…Evidently, only the lowest energy structures are investigated for the selected heterofullerenes. There are several relevant parameters, which influence relative stabilities of scrutinized structures including hybridization effect, strain effect, number and position of heteroatom(s), concentration, and solubility . We have divided our results and discussion section into the following 2 distinct parts.…”
Section: Resultsmentioning
confidence: 78%
“…2 and Table 1. Nevertheless, there are some experimental and computational studies revealing that the nitro derivative on fullerenes can be found [36,37]. Though, due to the chemically inert CNT system, the functionalization of NO 2 on the CNT sidewall should be more difficult than that of a fullerene surface.…”
Section: Nomentioning
confidence: 99%